One Decade of Research on Sustainable Investment Decision: A Systematic Literature Review - Sari, Pinkan Wulan; Aryani, Y Anni; Setiawan, Doddy (Universitas Negeri Malang, 2025)
This study aims to show empirical evidence on the development of investor decision research in sustainable investment for a decade from 2015 to 2024. This study uses the Scopus and SINTA 2 databases to select articles based on predetermined criteria so that 75 articles related to sustainable investment decisions are obtained, with details of 71 articles indexed by Scopus and four accredited by SINTA 2. This study uses the charting-the-field approach method by Hesford et al. (2006) by classifying articles based on journal name and topic and using Vosviewer software for keyword and author collaboration network analysis. The literature review results show that the Sustainability Journal dominates publishing articles on sustainable investment decisions. Returns, financial literacy, risk, attitudes toward sustainable investment, and environmental concerns are the main factors that influence sustainable investment decisions. In addition, gender and attitudes toward sustainable investment are the most important moderating and mediating variables for sustainable investment decisions. Socially Responsible Investment is the most widely used keyword in previous studies. Gutsche, Gunnar is the author with the most publications on the topic of sustainable investment decisions. This research provides knowledge regarding developing trends in sustainable investment decisions and opportunities for agendas for further researchers.